Conceptual approaches to the formation and development of creative industries in an inclusive economy - Khussainova, Zh.S.; Assanova, M.K.; Bektleyeva, D.E.; Abauova, G.M; Kankulov, M.K (BUKETOV BUSINESS REVIEW, 2023)
Object: Substantiate the potential of an inclusive economy for inclusive economic growth, determine the significance and place of creative industries in them and study country modifications of the creative economy in the context of inclusive development: industrial, post-industrial and innovative dominants. Methods: As a research methodology, the dialectical method of cognition and a systematic approach are used, revealing the possibilities of scientific research of socio-economic phenomena in the development of their interrelation and interdependence. Findings: The principles of social inclusiveness and the required components of the environment are identified. The scientific theoretical concepts of creative industries in inclusive economic growth are studied. The experience of building country modifications of the creative economy has been studied. The mechanism of inclusive economic growth as a result of the economic activity of all strata is determined, and the factors of its sustainability are determined. The advanced experience in the development of creative industries in the global space has been studied. Conclusions: Achieving maximum involvement in economic activity of labor resources and capital leads to a slowdown in economic growth. The main indicators of economic growth have the disadvantage of unequal participation in social production and unequal access to its results. Further stable sustainable economic growth is connected with the inclusion of all social strata in the economy. Engaging inclusive human capital requires creating the necessary environment. The change in the technological structure leads to an increase in the economic significance of intangible resources as a result of intellectual labor. The key to the development of creative industries is the cognitive abilities of people with a low dependence on the capital-labor ratio. The economy of network information creates additional opportunities for the comfort of communications. The creative economy and the inclusive economy dialectically accelerate each other’s development. Developing countries have developed creative clusters and become leaders in exports of creative goods. Geographically, the export of creative goods and the possession of intellectual property patents are dominated by Asian countries.